DEVELOPMENT OF A CHEMICALLY MODIFIED ELECTRODE BASED ON CARBON PASTE AND FUNCTIONALIZED SILICA-GEL FOR PRECONCENTRATION AND VOLTAMMETRIC DETERMINATION OF MERCURY(II) - Aleixo, L. M.; Souza, MDB; Godinho, OES; Neto, G. D.; Gushikem, Y.; Moreira, J. C. (Elsevier B.V., 1993)
A mercury-sensitive chemically modified electrode (CME) based on modified silica gel-containing carbon paste was developed. The functional group attached to the silica gel surface was 3-(2-thiobenzimidazolyl)propyl, which is able to complex mercury ions. This electrode was applied to the determination of mercury(II) ions in aqueous solution. The mercury was chemically preconcentrated on the CME prior to voltammetric determination by anodic stripping in the differential-pulse mode. A calibration graph covering the concentration range from 0.08 to 2 mg l-1 was constructed. The precision for six determinations of 0.122 and 0.312 mg l-1 Hg(II) was 3.2 and 2.9% (relative standard deviation), respectively. The detection limit for a 5-min preconcentration period was 0.013 mg l-1. A study for foreign ions was also made.
Keywords: VOLTAMMETRY; CARBON PASTE ELECTRODES; CHEMICALLY MODIFIED ELECTRODES; FUNCTIONALIZED SILICA GEL; MERCURY; PRECONCENTRATION